2015
DOI: 10.4093/dmj.2015.39.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Hexane Extract ofOrthosiphon stamineusInduces Insulin Expression and Prevents Glucotoxicity in INS-1 Cells

Abstract: BackgroundHyperglycemia, a characteristic feature of diabetes, induces glucotoxicity in pancreatic β-cells, resulting in further impairment of insulin secretion and worsening glycemic control. Thus, preservation of insulin secretory capacity is essential for the management of type 2 diabetes. In this study, we evaluated the ability of an Orthosiphon stamineus (OS) extract to prevent glucotoxicity in insulin-producing cells.MethodsWe measured insulin mRNA expression and glucose-stimulated insulin secretion (GSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
11
0
2
Order By: Relevance
“…Plant extracts or isolated natural products that potentiate glucose-stimulated insulin secretion by pancreatic β -cells can be investigated using several in vitro models such as perfused pancreas, isolated islets, and various β -cell lines. For instance, a perfused rat pancreas model [123] and the INS-1 pancreatic β -cell line [124] were used to investigate the effect Orthosiphon aristatus leaf extract on insulin secretion. Both studies reported that O. aristatus leaf extract stimulated glucose-induced insulin release in the perfused pancreas and in vitro [123, 124].…”
Section: Screening Plants and Natural Products For Antidiabetic Activitymentioning
confidence: 99%
“…Plant extracts or isolated natural products that potentiate glucose-stimulated insulin secretion by pancreatic β -cells can be investigated using several in vitro models such as perfused pancreas, isolated islets, and various β -cell lines. For instance, a perfused rat pancreas model [123] and the INS-1 pancreatic β -cell line [124] were used to investigate the effect Orthosiphon aristatus leaf extract on insulin secretion. Both studies reported that O. aristatus leaf extract stimulated glucose-induced insulin release in the perfused pancreas and in vitro [123, 124].…”
Section: Screening Plants and Natural Products For Antidiabetic Activitymentioning
confidence: 99%
“…Many signal pathways are involved in insulin expression and we investigated three of these in our IPCs: p38/MAPK [31], PI3K [32], and STAT-3 [33]. The enzyme inhibitors SB203580 and LY294002 were used to investigate the relationship between the MAPK/p38 and PI3K pathways in the differentiation process, throughout the induction period [34].…”
Section: Resultsmentioning
confidence: 99%
“…5 Kumis kucing (Orthosiphon stamineus) merupakan tanaman umum yang dijumpai di Asia Tenggara terutama di Indonesia, Malaysia, Thailand, Vietnam dan Myanmar. Tanaman ini dapat tumbuh sempurna dengan cahaya matahari penuh dan pada daerah beriklim hangat, namun juga bisa tumbuh di tanah yang lembab (Lee HJ, et al, 2015). Tingginya bisa mencapai 30-150 cm dan memiliki bunga berwarna putih, biru atau ungu.…”
Section: Pendahuluanunclassified
“…Ketika bunganya mekar, benang sari dan putiknya melebar jauh melampaui kelopak bunga yang menyerupai kumis kucing (Adnyana IK, dkk, 2013). Tanaman ini sering digunakan sebagai tumbuhan obat tradisional, di Indonesia tanaman tersebut dapat dijadikan teh (Lee HJ, et al, 2015). Kumis kucing (Orthosiphon stamineus) mempunyai efek sebagai anti diabetes, anti inflamasi, dan anti angiogenik (Adnyana IK, dkk, 2013).…”
Section: Pendahuluanunclassified